Emergent properties from first principles: d0 magnetism and metal-insulator transitions - Walber Hugo de Brito (2016)
In this thesis we employed electronic structure methods to investigate emergent properties of dierent materials, namely d0 magnetism in carbon based materials and metal insulator transitions in transition-metal oxides. In the rst part, we investigated (i) the morphology, relative energetic stability, electronic, and magnetic properties of graphenelike carbon nitride structures and (ii) the structural, energetics, electronic, and magnetic properties of polytetrauoroethylene (Teon) crystals with uorine vacancies and oxygen impurities. In the second part we studied (iii) the metal-insulator transition in vanadium and niobium dioxides, with focus on the physical mechanism responsible for the gap formation in their low-temperature phases.In (i) we obtained a set of low-energy graphene-like structures with distinct nitrogen concentrations. In particular, we identied that their relative stability is associated with the energy cost due to the charge doping induced by the nitrogen impurities. In addition, new semiconducting and ferromagnetic carbon nitride structures were proposed. In (ii) we obtained that both uorine vacancies and oxygen impurities in bulk Teon lead to structural congurations without the breaking of the carbon backbone. Oxygen impurities were found to be energetically more stable than uorine vacancies. In addition, the formation of polyconjugated structures in the polymer chain was foundto be energetically favorable. The local magnetic moments associated with the point defects do not give rise to any ferromagnetic ordering, which rules out the investigated congurations as the origin of ferromagnetism in defective Teon tapes. Finally, in (iii) we proposed a new mechanism for the gap opening in the lowtemperature phases of VO2 and NbO2. We identied that Mott physics is central for theproper description of all phases of VO2 since its electrons are in the near vicinity of the Mott transition. In the M1 phase and in the antiferromagnetically ordered M2 phase, we found that the Mott-Hubbard instability is arrested due to V-atoms dimerization and antiferromagnetic ordering, respectively. In especial, we obtained that nonlocal electronic correlations support the gap opening in the low-temperature phases. Hubbard instabilities were found only in the case of undimerized V-atoms of the paramagnetic M2 phase. In respect to NbO2, we found that electronic correlations are less important, though they do play a role in the gap opening of its low-temperature phase.